2013
DOI: 10.1097/mcp.0b013e3283606ab5
|View full text |Cite
|
Sign up to set email alerts
|

The increasing incidence of empyema

Abstract: Continued surveillance in the epidemiology of empyema is needed. Progress in new strategies of prevention, such as a new generation of conjugate pneumococcal vaccines and protein-based vaccines, could become an important step in the control of this important complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 61 publications
1
61
1
6
Order By: Relevance
“…Serotypes 1 and 3 have been associated with empyema, and because they are not included in PCV7, serotype replacement may cause increased rates of empyema after vaccine introduction. 36 An increase in staphylococcal empyema or empyema of unknown etiology has been described, as well as an increase in pneumonia complicated by empyema, from 3.7 cases per 100 000 children to 10.3 after vaccine introduction in the United States. [35][36][37] As was found in earlier studies, we found a nearly twofold increase in hospitalizations for empyema in children aged ,2 years; this was nonsignificant, probably because of low numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotypes 1 and 3 have been associated with empyema, and because they are not included in PCV7, serotype replacement may cause increased rates of empyema after vaccine introduction. 36 An increase in staphylococcal empyema or empyema of unknown etiology has been described, as well as an increase in pneumonia complicated by empyema, from 3.7 cases per 100 000 children to 10.3 after vaccine introduction in the United States. [35][36][37] As was found in earlier studies, we found a nearly twofold increase in hospitalizations for empyema in children aged ,2 years; this was nonsignificant, probably because of low numbers.…”
Section: Discussionmentioning
confidence: 99%
“…36 An increase in staphylococcal empyema or empyema of unknown etiology has been described, as well as an increase in pneumonia complicated by empyema, from 3.7 cases per 100 000 children to 10.3 after vaccine introduction in the United States. [35][36][37] As was found in earlier studies, we found a nearly twofold increase in hospitalizations for empyema in children aged ,2 years; this was nonsignificant, probably because of low numbers. The highest incidence of empyema was observed in 2007 to 2009, immediately after introduction of PCV7, indicating that factors other than the vaccine may have contributed.…”
Section: Discussionmentioning
confidence: 99%
“…Most pediatric empyema cases are due to S pneumoniae; however, even with the emergence of heptavalent proteinpolysaccharide conjugate vaccine, the incidence of empyema in children under two doubled after its release; the rates among children aged 2e4 nearly tripled [6], prompting development of a 13-valent pneumococcal vaccine in 2010. Since that time there has been evidence that complicated pneumococcal pneumonia may be declining [7].…”
Section: Discussionmentioning
confidence: 97%
“…The incidence of ET seems to have been increasing both in children and adults worldwide. [8] Peak incidence of ET between 21-40 yrs. age had been reported in previous studies.…”
Section: Types Of Underlying Diseasementioning
confidence: 99%